Enhanced fano-type broadband acoustic ventilated silencer with arbitrary geometrical configurations - Xu, Zi-xiang; Fang, Yu; Wang, Xiao-ping (Frontiers in Physics, 2025)
The introduction of Fano resonance into acoustic metamaterials provides the possibility for simultaneous airborne sound insulation and high-efficiency ventilation, while the ultranarrow Fano line shape and limited shape configurations restrict the expansion to practical applications. In this work, we theoretically propose and demonstrate a broadband low-frequency ventilation acoustic chiral barrier with arbitrary geometrical configurations, where consecutive multiple Fano resonances (CMFRs) generate destructive interference in the range of 479–1,032 Hz. The barrier unit with a binary planar design is composed of the chiral space-coiling tunnel and hollow pipe, providing the discrete resonant and continuum states for Fano resonant system. By means of judiciously tuning the coupling of the above-mentioned two states, multi-order Fano resonances manifest as low transmission in a wide frequency range. Good agreement between simulated, theoretical, and measured results validates the effectiveness of the proposed barrier in the broad low-frequency range, in which the laminar and turbulent flow models reveal the high air-permeability of our barrier. Thanks to the unit planar profile, we can flexibly customize the arbitrary geometrical configurations of the barrier to extend into three-dimensional (3D) space for practical noise reduction applications. Our research makes it possible to construct ventilation artificial metastructure with a flexible manner for broadband sound attenuation.